PREVENTIVE MEASURES IN PHYSICAL THERAPY FOR THE RECOVERY OF YOUNG STUDENTS WITH COMPUTER NECK SYNDROME (Physical Culture and Sport: Scientific Perspective, 2025)
The purpose of this article was to analyze the impact of gadget use on the formation of neck and shoulder pain and headaches in university students and to suggest preventive measures in physical therapy for individuals with computer neck syndrome.Taking into account the above it is relevant and appropriate to pay attention to this issue and propose preventive measures in physical therapy for the recovery of patients with computer neck syndrome using therapeutic exercises to ensure increased efficiency of the recovery process.The implementation of preventive measures in physical therapy for people with computer neck syndrome is based on a patient-oriented choice of intervention methods aimed at solving primarily problems that cause limitations in everyday life. A clearly defined combination of various measures helps to improve efficiency and achieve the set goals faster, as well as interest and motivate patients, improves the psycho-emotional state in classes, which will contribute to a more active involvement in motor activity during the day.Using an integrated approach from the family, educational institutions, and healthcare to prevent the development of this syndrome, as well as including a course in the curriculum to familiarize students with the possible negative consequences of excessive use of gadgets on their health.
Keywords: students; preventive measures; computer neck syndrome; physical therapy